High throughput screening of fungal phytopathogens caught in Australian forestry insect surveillance traps - Trollip, Conrad; Carnegie, Angus J.; Piper, Alexander M.; Kaur, Jatinder; Martoni, Francesco; Dinh, Quang; Smith, David; Mann, Ross; Rodoni, Brendan; Edwards, Jacqueline (Frontiers in Forests and Global Change, 2023)
Post-border surveillance for forestry’s high priority pests and pathogens is conducted routinely through established programs focused on the main points-of-entry and across the major plantation growing regions. Currently, most diagnostic protocols used to identify fungal phytopathogens sampled during these surveys rely on traditional methods, such as morphological examination and DNA barcoding techniques. This stepwise process from isolation to species identification is often regarded as slow, expensive, and limited due to the need for disease manifestation and/or comprehensive expertise for rapid and accurate detection. In this study, we applied a recently validated high-throughput, dual-marker amplicon sequencing approach on insect surveillance traps from across Australia to assess its performance for the targeted surveillance of the Ophiostomatales, an order of fungi comprising notable phytopathogens which are vectored by bark beetles. By using a recently validated assay we were able to confidently characterize a range of Ophiostomatalean taxa known to be present in Australia, while reporting eight first detections from environmental DNA. Our study demonstrates the value of targeted multi-barcode amplicon sequencing for high-throughput screening of fungi caught in post-border surveillance traps, in addition to emphasizing research priorities that require further investigation before such methods can be implemented routinely for biosecurity.